Factors affecting the geoeffectiveness of shocks and sheaths at 1 AU. Issue 11 (10th November 2016) - Lugaz, N.; Farrugia, C. J.; Winslow, R. M.; Al‐Haddad, N.; Kilpua, E. K. J.; Riley, P.
Abstract: We identify all fast‐mode forward shocks, whose sheath regions resulted in a moderate (56 cases) or intense (38 cases) geomagnetic storm during 18.5 years from January 1997 to June 2015. We study their main properties, interplanetary causes, and geoeffects. We find that half (49/94) such shocks are associated with interacting coronal mass ejections (CMEs), as they are either shocks propagating into a preceding CME (35 cases) or a shock propagating into the sheath region of a preceding shock (14 cases). About half (22/45) of the shocks driven by isolated transients and which have geoeffective sheaths compress preexisting southward B z . Most of the remaining sheaths appear to have planar structures with southward magnetic fields, including some with planar structures consistent with field line draping ahead of the magnetic ejecta. A typical (median) geoeffective shock‐sheath structure drives a geomagnetic storm with peak Dst of −88 nT pushes the subsolar magnetopause location to 6.3  R E, i.e., below geosynchronous orbit and is associated with substorms with a peak AL index of −1350 nT. There are some important differences between sheaths associated with CME‐CME interaction (stronger storms) and those associated with isolated CMEs (stronger compression of the magnetosphere). We detail six case studies of different types of geoeffective shock‐sheaths, as well as two events for which there was no geomagnetic storm but other magnetospheric effects. Finally, we discuss our results in terms of space weather forecasting and potential effects on Earth's radiation belts. Key Points: Forty‐nine shocks/sheaths in a previous transient and 45 isolated shocks drove moderate or intense geomagnetic storms from 1997 to 2015 Fifty percent of shocks in transients and 13% of shocks in normal solar wind had a sheath region that drove at least a moderate storm A median geoeffective shock/sheath pushed the magnetopause to 6.3 RE, had strong substorms ( AL  = ‐1350 nT) and moderate storm ( Dst  = ‐88 nT)